TINGKAT PENDAPATAN PETERNAK PADA PENGGEMUKAN SAPI BALI DENGAN SISTEM BAGI HASIL DI KABUPATEN KUPANG - Johanis A. Jermias; Defrys R. Tulle; Cardial L.O. Leo-Penu; I.G.N. Jelantik (Politeknik Pertanian Negeri Kupang, 2010)
Income Level of Farmers on Fattening Bali Cattle using Profit Share System. The research conducted during 10 months in 2009 and aimed to identify the contribution of income from fattening cattle farmers and to determine the factors affecting the level of income from such business. Sixty farmers were taken as respondents by purposive random sampling in Amarasi, Kupang regency. Data were collected through interviews with respondents and were continued with inputoutput analysis and statistical analysis using correlation analysis, regression analysis, and is equipped with the calculation of the coefficient of multiple determinations (R2). The results showed that the business was able to provide cash income to farmers amounted to Rp 281,303.08; simultaneously, the income is influenced significantly (P<0.01) by the number of fattened cattle, cattle’s age, length of fattening period, the cost of cattle’s feed, and labor costs, with a coefficient of multiple determination (R2) amounted to 85.6%.Key words: Farmer income, Bali Cattle, Fattening and Profit Share